General practice data retrieval: the Northern Ireland project. (August 1995) - Boydell, L; Grandidier, H; Rafferty, C; McAteer, C; Reilly, P
Abstract : OBJECTIVE--To develop an epidemiological database of morbidity in the community as presented to general practitioners and to support epidemiological research in general practice. DESIGN--The project is a sentinel network of 23 general practices in Northern Ireland that report the incidence of a list of selected diseases to a central unit for analysis. RESULTS--Results are presented for depression, diabetes, and myocardial infarction. The age--sex distributions of diabetes and myocardial infarction are comparable with other published data but the incidence of depression is under estimated. CONCLUSIONS--The importance of complete accuracy of data reported within sentinel networks depends on the purposes for which information is to be used. For some diagnoses, such as diabetes and acute myocardial infarction, the accuracy of the reported incidence is high while for other diseases, such as depression, where diagnostic behaviour varies more between doctors, the figures are much less reliable.